Five smooth stones - Gregory, Kristiana (New York Scholastic, 2001)
In her diary, a young girl writes about her life and the events surrounding the beginning of the American Revolution in Philadelphia in 1776.
Sequel: We are patriots.
Keywords: Philadelphia (Pa.) -- History -- Revolution, 1775-1783 -- Juvenile fiction